2010
DOI: 10.1007/s11200-010-0035-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and Archeointensity of Earth’s magnetic field recovered from El Opeño, earliest funeral architecture known in Western Mesoamerica

Abstract: Despite of the impressive cultural heritage and abundant archaeological sites, absolute geomagnetic intensity data from Mesoamerica are still sparse. Archeointensity determinations using the Coe variant of the Thellier and Thellier method have been carried out on some selected pottery fragments from the El Opeño archeological site which has the earliest funeral architecture known in western Mesoamerica. The El Opeño chronology is supported by six C 14 datings performed on carbon-bearing materials. Detailed roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…7b), although the mean VADMs per site are consistently below the 10-point moving average through the Levant-data -at least until 723 BC. For the period between ∼1050-500 BC, paleointensity data from other parts of the world are sparse; for Mexico VADMs of ∼82 (Pétronille et al, 2012) and ∼105 ZAm 2 (Duran et al, 2010) are suggested and Yu (2012) and Hong et al (2013) report VADMs of ∼80-90 ZAm 2 for Japan and South Korea, respectively, around ∼750 BC. All reported values are much lower than the values reported for the Middle East (>150 ZAm 2 ) and the Canary Islands (∼125 ZAm 2 ).…”
Section: Spatial and Temporal Extent Of The Levant Intensity Highmentioning
confidence: 99%
“…7b), although the mean VADMs per site are consistently below the 10-point moving average through the Levant-data -at least until 723 BC. For the period between ∼1050-500 BC, paleointensity data from other parts of the world are sparse; for Mexico VADMs of ∼82 (Pétronille et al, 2012) and ∼105 ZAm 2 (Duran et al, 2010) are suggested and Yu (2012) and Hong et al (2013) report VADMs of ∼80-90 ZAm 2 for Japan and South Korea, respectively, around ∼750 BC. All reported values are much lower than the values reported for the Middle East (>150 ZAm 2 ) and the Canary Islands (∼125 ZAm 2 ).…”
Section: Spatial and Temporal Extent Of The Levant Intensity Highmentioning
confidence: 99%
“…One‐third of the initial Mexican data set was accepted: six lava flows (Alva‐Valdivia et al., 2019; Gratton et al., 2005; Mahgoub, Juárez‐Arriaga, Böhnel, Siebe, & Pavón‐Carrasco, 2019; Morales et al., 2006; Pérez Rodriguez et al., 2019) and 39 baked clays (Alva‐Valdivia et al., 2021; Hervé, Perrin, Alva‐Valdivia, Tchibinda Madingou, et al., 2019; Mahgoub, Juárez‐Arriaga, Böhnel, Manzanilla, & Cyphers, 2019). Other high‐quality archeomagnetic data exist in Mexico, but they are either beyond the 2,000 km limit (e.g., Fanjat et al., 2013) or older than 2 kyrs (e.g., Duran et al., 2010; Hervé, Perrin, Alva‐Valdivia, Rodríguez‐Trejo, et al., 2019). For Western North America, 47% of the data set passed the selection criteria, with one lava flow (Champion, 1980) and 23 data on ceramics (Bowles et al., 2002; Jones et al., 2020; Sternberg, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Over the 194 available in Mexico, only 14 data, eight from Duran et al (), three from Rodriguez‐Ceja et al (), and three from Rodriguez‐Ceja et al (), fulfilled the quality criteria for the period between 2000 BCE and 200 CE. Intensities of Rodriguez‐Ceja et al (, ) calculated on a secondary or two overlapping components of magnetization were not considered.…”
Section: Discussionmentioning
confidence: 99%